Dodecyl creatine ester and lipid nanocapsule: a double strategy for the treatment of creatine transporter deficiency. (2015) - Trotier-Faurion, Alexandra; Passirani, Catherine; Béjaud, Jérôme; Dézard, Sophie; Valayannopoulos, Vassili; Taran, Fréderic; de Lonlay, Pascale; Benoit, Jean-Pierre; Mabondzo, Aloïse
Background: Creatine transporter (CT) deficiency is characterized by mutations in the gene encoding CT, leading to impaired transport of creatine at the cell membrane. Patients with this disease would thus benefit from replenishment of creatine inside the brain cells.Aim: We report a therapeutic strategy based on the use of dodecyl creatine ester incorporated into lipid nanocapsules (LNCs).Materials & methods: The dodecyl creatine ester was incorporated in the shells of LNCs using Transcutol ® (Gattefossé SAS, Saint-Priest, France). The interactions of dodecyl creatine ester encapsulated in LNCs with an in vitro cell-based blood–brain barrier model was studied. The entry of the dodecyl creatine ester encapsulated in LNCs and the conversion of dodecyl creatine ester to creatine in the cells were also studied in the pathological context of CT deficiency.Results & discussion: We showed that these LNCs can cross the blood–brain barrier and enter brain endothelial cells. In human fibroblasts lacking functional CT, all or part of the dodecyl creatine ester was released from the LNCs and biotransformed to creatine, thus indicating the value of this strategy in this therapeutic context. Original submitted 2 April 2013; Revised submitted 28 October 2013